Defining "Religion" and "Atheism" - Oppy, Graham 1960- (2021)
There are various background issues that need to be discussed whenever the topic of conversation turns to religion and atheism. In particular, there are questions about how these terms are to be used in the course of the conversation. While it is sometimes the case that all parties to a conversation about religion and atheism have agreed what they mean by "religion" and "atheism", it is often enough the case that such conversations go poorly because the parties mean different things by "religion" and "atheism". In this paper, I discuss a range of questions about the meanings of "religion" and "atheism" that should be taken into account when we are asking global questions about "religion" and "atheism".